Active Case Finding for Improved Ebola Virus Disease Case Detection in Nimba County, Liberia, 2014/2015: Lessons Learned - E. Namukose; C. Bowah; I. Cole; G. Dahn; P. Nyanzee; R. Saye; M. Duworko; P. Nsubuga; M. Mawanda; N. Mahmoud; P. Clement; T. D. Ngabirano; et al. (Advances in Public Health)
Objectives. Early case detection and isolation of patients infected with highly infectious diseases are crucial in the management and control of epidemics such as Ebola Virus Disease (EVD). In this paper, we share the lessons learned from implementation of active case finding as a strategy for improved EVD case detection in Nimba County, Liberia. Methods. We adopted the World Health Organization (WHO) active surveillance strategy to identify and report suspected EVD cases, follow up contacts of confirmed cases, and report community deaths. We identified, trained, and deployed 1060 Community Health Volunteers (CHVs) in 718 communities in Nimba County. The CHVs were supervised by 142 health workers within their catchment area. The health workers were supervised by the District Health Officers (DHOs). The DHOs reported to the County Health Team (CHT) who provided supportive supervision. Data collection was based on the EVD contact tracing and active case finding forms adopted from WHO. Data analysis was based on epi-weeks. Results. The number of EVD suspected cases increased by more than 75% following the initiation of active case finding. Average duration between symptom onset and case detection reduced from between three and five days to within 24 hours. Collection of oral swabs from dead bodies increased from two to 15 within the first week of active case finding strategy implementation. Reporting of other IDSR priority diseases and conditions also improved. Conclusion. Active case finding strategy in Nimba increased suspected EVD case detection and reduced the duration between onset of symptoms and detection of cases.